2010
DOI: 10.1363/3614910
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Female Condoms to Female Sex Workers in Central America

Abstract: The female condom could play an important role in reducing HIV infection among female sex workers and their clients in Central America. Acceptability studies have shown that Central American sex workers are amenable to using the female condom, 1-3 but programs have not always successfully promoted long-term use. For example, promotional efforts by the Pan American Social Marketing Organization (PASMO) produced different results in different countries in the region: In Nicaragua in 2005, only 300 female condoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…6 Most of the eight studies reviewed took place in developing countries and/or higher HIV-prevalence settings. Findings suggest that female condoms can be sexually acceptable to many women (especially sex workers) by way of enhanced level of lubrication (Mack, Grey, Amsterdam, Williamson, & Matta, 2010;Mathenjwa & Maharaj, 2012), greater pleasure and sensation than the male condom (Mathenjwa & Maharaj, 2012), clitoral stimulation through the outer ring (Mathenjwa & Maharaj, 2012), capacity to comfortably accommodate all penis sizes (Mack et al, 2010), ability to insert prior to sexual activity (Mathenjwa & Maharaj, 2012), and better smell than male condoms (Mack et al, 2010). Indeed, women's experiences of greater pleasure and sexual sensations helped predict long-term use of female condoms among 255 women in Brazil (Telles Dias, Souto, & Page-Shafer, 2006).…”
Section: Female Condommentioning
confidence: 97%
See 2 more Smart Citations
“…6 Most of the eight studies reviewed took place in developing countries and/or higher HIV-prevalence settings. Findings suggest that female condoms can be sexually acceptable to many women (especially sex workers) by way of enhanced level of lubrication (Mack, Grey, Amsterdam, Williamson, & Matta, 2010;Mathenjwa & Maharaj, 2012), greater pleasure and sensation than the male condom (Mathenjwa & Maharaj, 2012), clitoral stimulation through the outer ring (Mathenjwa & Maharaj, 2012), capacity to comfortably accommodate all penis sizes (Mack et al, 2010), ability to insert prior to sexual activity (Mathenjwa & Maharaj, 2012), and better smell than male condoms (Mack et al, 2010). Indeed, women's experiences of greater pleasure and sexual sensations helped predict long-term use of female condoms among 255 women in Brazil (Telles Dias, Souto, & Page-Shafer, 2006).…”
Section: Female Condommentioning
confidence: 97%
“…Initially, women in one study reported that the method's design, particularly the internal ring, made it difficult (and painful) to insert and remove. However, after several uses, more than half of participants preferred the female to the male condom (Mack et al, 2010). Among female condom users, the most common complaint (30%) was poor sexual satisfaction associated with use.…”
Section: Higgins and Smithmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, female condoms are the only woman-controlled HIV prevention option, but they are detectable and may require partner consent. They are also less available and more expensive than male condoms (Mack et al 2010). …”
Section: Case Study: Hiv Microbicidesmentioning
confidence: 99%
“…While many risk factors have been associated with hiv/aids infection rates, several studies have linked the spread of infection among the African American female population to knowledge, awareness, and the gender ratio imbalance among African American women and African American males (Broaddus, Morris, & Bryan, 2010;Laub, Somera, Gowen, & Diaz, 1999;Weeks, Coman, Hilario, Li, & Abbott, 2013). Considerable research suggests that a relationship exists between female condom usage, acceptability, and gender dynamics (Mack, Grey, Amsterdam, Williamson, & Matta, 2010;Small, Weinman, Buzi, & Smith, 2010;Wingood & DiClemente, 2000).…”
mentioning
confidence: 99%